Drug utilization study and safety profile of iron isomaltoside 1000 in treatment of iron deficiency anemia in cancer patients: a retrospective study - Paul, Davinder; Mahajan, Manish; Bharat, Suyash; Tripathi, Richa (International Journal of Research in Medical Sciences, 2025)
Background: Anemia is prevalent among cancer patients, affecting 39.3% to 63.4%, depending on the diagnostic threshold used. Cancer treatments often exacerbate anemia, significantly impacting patients' quality of life. In 2019, Feruno (Iron Isomaltoside 1000) was introduced in India for rapid intravenous infusion, offering controlled and gradual iron release, thereby reducing toxicity risks. Studies have confirmed its safety, effectiveness, and tolerability across various patient populations. Methods: This single-centre, retrospective drug utilization study evaluated Iron Isomaltoside 1000 (Feruno) in 98 cancer patients with iron deficiency anemia. Results: The mean age of patients was 56 years, with breast, ovarian, and colon cancers being the most common. The average iron requirement was 1,396.9 mg, and the most frequently administered dosage was 1,000 mg. The treatment was effective and well-tolerated, with minimal adverse reactions. Conclusions: Iron Isomaltoside demonstrated a good safety profile. The iron requirement in cancer patients is usually above 1 gram, and the most frequently prescribed dose was 1,000 mg. To improve patient compliance and leverage the benefit of a higher dose (20 mg/kg body weight) administered in a single infusion, most patients can be treated effectively with a total dose infusion.